Islam Aboge: Islam and Cultural Java Dialogue (A Study of Islam Aboge Communities in Ujungmanik, Cilacap, Central Java, Indonesia) - Abdurrahman Misno Bambang Prawiro (UIN Sunan Gunung Djati Bandung, 2013)
Islam came to Java in which the state population has a form of cultural traditions and belief in the power of certain objects (dynamism), the strength of the spirit of the deceased (animism) and belief in the power of the animals (Totemism). This tradition has been passed from generation to generation; it is believed and practiced in daily life. So when Islam came, confidence and trust is dissolved into the Islamic culture. Therefore comes the so-called Islamic syncretism that is acculturation with Islamic tradition. Among the forms of local acculturation (Java) with Islam is a tradition embraced by the Muslim Aboge community in the village of Ujungmanik Kawunganten Cilacap district, Central Java province, Indonesia. These community traditions carry with spiced Javanese Islamic tradition, the Islamic came with local flavor.The specificity of this community are still use the models of Javanese Islamic calendar (calendar Aboge (Alip Rebo Wage)) to determine the beginning of Ramadan, Idhul Fithri and Idhul Adha. Because of the using of the calendar, so that the celebrations of Ramadhan, Idhul Fitri and Idhul Adha is always different to what has been set by the government. This article discusses Islam and Javanese acculturation on Aboge Islamic Community and the dating models they use. With the approach of phenomenology and interpretation of cultural studies in the frame of ethnography, it is expected to make clear this acculturation models.